2016
DOI: 10.1111/jph.12522
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Bacillus amyloliquefaciens IBFCBF‐1 with Potential for Biological Control of Phytophthora Blight and Growth Promotion of Pepper

Abstract: In this study, 76 bacterial strains were isolated from the rhizosphere soil of pepper. Of these, 23 bacterial isolates capable of inhibiting Phytophthora capsici growth were selected. Among the antagonistic bacteria, one strain, IBFCBF‐1 showed the strongest antagonistic activity, and was identified as Bacillus amyloliquefaciens based on the results of 16S rRNA gene sequence analysis, physiological and biochemical testing, and morphological characteristics. When tested with a dual‐culture method and with labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
3
10
0
1
Order By: Relevance
“…This increase in height remained consistent until the late stages of growth, the non-treated plants catching up with the growth of the 260-02: gfp treated plants, though there was still a statistically significant difference in height. The increase in height of the treated peppers was around 20%, in line with earlier results obtained with growth promoters (Kang et al, 2007; Zhang et al, 2016).…”
Section: Resultssupporting
confidence: 90%
“…This increase in height remained consistent until the late stages of growth, the non-treated plants catching up with the growth of the 260-02: gfp treated plants, though there was still a statistically significant difference in height. The increase in height of the treated peppers was around 20%, in line with earlier results obtained with growth promoters (Kang et al, 2007; Zhang et al, 2016).…”
Section: Resultssupporting
confidence: 90%
“…), wheat (root rot, leaf blight, etc. ), and other crop diseases ( Baker et al, 1983 ; Wilson and Pusey, 1985 ; Lin et al, 2001 ; Chan et al, 2003 ; Souto et al, 2004 ; Ouhaibi-Ben Abdeljalil et al, 2016 ; Zalila-Kolsi et al, 2016 ; Zhang M. et al, 2016 ; Fan et al, 2017b ; Gómez Expósito et al, 2017 ; Qin et al, 2017 ; Barratt et al, 2018 ; Wang X. Q. et al, 2018 ). Ramírez et al (2021) isolated a B. cereus MH778713 from root nodules of Prosopis laevigata , and the volatile hentriacontane and 2,4-di-tert-butylphenol produced by it can effectively inhibited the radial growth of F. oxysporum and protected tomato plants against Fusarium wilt .…”
Section: Discussionmentioning
confidence: 99%
“… Mutaz Al-Ajlani and Hasnain (2010) determined that 54 of 118 Bacillus strains isolated from soil samples had antagonistic activities toward at least two strains from a panel of pathogenic and non-pathogenic microorganisms. Zhang M. et al (2016) isolated Bacillus amyloliquefaciens IBFCBF-1 that can effectively control Phytophthora blight and promote the growth of pepper. Singh et al (2008) found that B. subtilis BN1 isolated from the chir pine ( Pinus roxburghii ) rhizosphere exhibited strong antagonistic activity toward F. oxysporum and R. solani .…”
Section: Introductionmentioning
confidence: 99%
“…Following this line of research, several microbial genera have been proposed for their role in specific disease suppressiveness. These include (fluorescent) Pseudomonas ( Kloepper et al, 1980 ; Scher and Baker, 1980 , 1982 ; Wong and Baker, 1984 ; Lemanceau and Alabouvette, 1991 ; Raaijmakers and Weller, 1998 ; De Souza et al, 2003 ; Perneel et al, 2007 ; Mazurier et al, 2009 ; Mendes et al, 2011 ; Michelsen and Stougaard, 2011 ), Streptomyces ( Liu et al, 1996 ; Cha et al, 2016 ), Bacillus ( Sneh et al, 1984 ; Cazorla et al, 2007 ; Abdeljalil et al, 2016 ; Zhang et al, 2016 ), Paenibacillus ( Haggag and Timmusk, 2008 ), Enterobacter ( Schisler and Slininger, 1994 ; Abdeljalil et al, 2016 ), Alcaligenes ( Yuen and Schroth, 1986 ), Pantoea ( Schisler and Slininger, 1994 ), non-pathogenic F. oxysporum ( Sneh et al, 1987 ; Couteaudier and Alabouvette, 1990 ; Larkin et al, 1996 ; Larkin and Fravel, 2002 ; Nel et al, 2006 ; Mazurier et al, 2009 ; Raaijmakers et al, 2009 ), Trichoderma ( Harman et al, 1980 ; Liu and Baker, 1980 ; Chet and Baker, 1981 ; Hadar et al, 1984 ; Smith et al, 1990 ; Mghalu et al, 2007 ), Penicillium janczewskii ( Madi and Katan, 1998 ), V. biguttatum ( Jager and Velvis, 1983 ; Velvis and Jager, 1983 ), Pochonia chlamydosporia ( Yang et al, 2012 ), Clonostachys / Gliocadium ( Smith et al, 1990 ; Rodríguez et al, 2015 ) and P. oligandrum ( Martin and Hancock, 1986 ).…”
Section: Old and New Approaches To Study Disease Suppressive Soilsmentioning
confidence: 99%